A Check List of Important Mammalian Species Observed in and around Chilkiya-kota Elephant (Dhangari-sunderkhal) Corridor, an Important Wildlife Corridor in Corbett Landscape in Uttarakhand, India - Kundu, Sumanta; Ansari, A. G.; Mauriya, Vipul; Bargali, H. S. (Indian Forester, 2018)
The Chilkiya-Kota Elephant Corridor (Dhangari-Sunderkhal) is a vital wildlife corridor in Corbett Landscape, Uttarakhand, India facilitating connectivity between the Corbett Tiger Reserve (CTR) and Ramnagar Forest Division part of which is being blocked due to encroachment. A list important mammalian species observed in and around this vital wildlife corridor is compiled for strengthening the need of securement and longterm conservation of this vital corridor for unhindered movement and dispersal of various wildlife.